GENIUS LOCI PADA PERKAMPUNGAN TRADISIONAL SENARU SUKU SASAK KABUPATEN LOMBOK BARAT - Ersina, Sriany; Amalia, Annisa; Sutriani, Sutriani (Nature : National Academic Journal of Architecture, 2014)
Senaru traditional village located in Senaru Village Lombok West Regency. The existence of a traditional village in response to the demands of home and village which is a form of cohabitation of Sasak as the original inhabitants of this village. Literally, the genius loci is the soul of space and time, locality and region-region where architecture grows and develops that triggers the growth of the spirit of "place" (spirit of place) where the spirit that makes a place that can "live". The genius loci in this study is divided into two, namely the genius loci of the settlement area and genius loci in neigborhood of the traditional village of Sasak tribe in the village of Senaru.